Panhypopituitarism Without GH Replacement: About Insulin Sensitivity, CRP Levels, and Metabolic Syndrome - Castillo, Alejandro Rosell; Zantut-Wittmann, Denise Engelbrecht; Neto, Arnaldo Moura; Jales, Rodrigo Menezes; Garmes, Heraldo Mendes (Hormone and Metabolic Research, 2018)
A complete deficiency of anterior pituitary hormones from several etiologies characterizes Panhypopituitarism (PH). Despite advances in treatment, patients with PH maintain high rates of morbidity and mortality, a reason to investigate some insulin sensitivity, metabolic and inflammatory parameters that could be related to the increase of these indicators. This was a cross-sectional study comprising 41 PH patients under hormonal replacement, except for growth hormone, and 37 individuals in a control group (CG) with similar age, gender and body mass index (BMI). We assessed clinical data as age, sex, BMI, waist circumference, waist/hip ratio (WHR), history of hypertension, diabetes mellitus and dyslipidemia as well as fasting glycaemia, insulin, HOMA-IR, HbA1c, high-sensitivity CRP (hs-CRP), and lipid profile. PH patients presents lower values of glycaemia, insulin, HOMA-IR (0.88 vs 2.1) and WHR, but higher levels of hs-CRP (0.38 vs 0.16mg/dl) when compared with the CG. Although the occurrence of dyslipidemia was higher in patients with PH, the frequency of metabolic syndrome was similar between the groups. In multivariate linear regression analysis, the PH group independently predicted lower HOMA-IR and WHR values. In conclusion, this study demonstrated that patients with PH without GH replacement have lower HOMA-IR and WHR values and higher levels of hs-CRP than a CG paired by age, gender and BMI. The diagnosis of dyslipidemia was more frequent in patients with PH, but the occurrence of MS was similar to CG. Further studies are needed to confirm our findings and to better understand the metabolic characteristics of patients with PH.
Keywords: insulin resistance; hypopituitarism; inflammatory activity; dyslipidemia